(untitled) - Gillies, Andrew (London, 2017)
Note-taking for Consecutive Interpreting: A Short Course is the essential step-by-step guide to the skill of note-taking. The system, made up of a range of tried and tested techniques, is simple to learn, consistent and efficient. Each chapter presents a technique, with examples, tasks and exercises.
Keywords: Biên phiên dịch,Translating and interpreting